Integrating SDGs into Problem-Based Learning on the Climate Change Material to Strengthen Students’ Science Literacy and Learning Motivation - Maulina, Dina; Dewi, Pramita Sylvia; Meriza, Nadya; Riyanti, Marisky Catur; Ibrahim, Nor Hasniza; Abdurrahman; Fathimah, Ismah (Universitas Islam Negeri Raden Intan Lampung, 2026)
Integrating the Sustainable Development Goals (SDGs) into climate change instruction can provide an authentic context for Problem-Based Learning (PBL) and may enhance students’ scientific literacy and learning motivation. This quasi-experimental study employed a non-equivalent control-group pretest–posttest design with 65 tenth-grade students from SMA Muhammadiyah 2 Bandar Lampung (Indonesia), selected through purposive sampling. The experimental group learned through SDG-oriented PBL, while the control group received guided inquiry instruction. Data were collected using a scientific literacy test and a learning motivation questionnaire; interviews and a student response questionnaire were used to enrich interpretation. Learning gains were calculated using normalized gain (N-gain). Because the data violated normality and homogeneity assumptions, group differences were tested using the Mann–Whitney U test, followed by effect size estimation and correlation analysis. The experimental group achieved a moderate improvement in scientific literacy (N-gain = 0.55) with a large effect size (0.63) and higher post-intervention learning motivation (M = 82.00). A firm positive relationship was observed between scientific literacy and learning motivation (r = 0.97, p < .001). Overall, SDG-oriented PBL on climate change shows promise for strengthening students’ scientific literacy and learning motivation. The findings suggest that integrating SDGs into science education can be an effective strategy for improving both students’ cognitive and affective learning outcomes, providing implications for educators to adopt context-based and meaningful learning approaches in teaching climate change and other global challenges.